Hierarchical poly(p-phenylene benzobisoxazole)/graphene oxide reinforcement with multifunctional and biomimic middle layer. (September 2016) - Chen, Lei; Du, Yunzhe; Huang, Yudong; Wu, Feng; Cheng, Hei Man; Fei, Bin; Xin, John H.
Graphical abstract: Abstract: A new hierarchical reinforcement developed by coating biomimic polydopamine (PDA) on the surface of poly( p -phenylene benzobisoxazole) (PBO) fibers, which served as a platform for the graphene oxide (GO) grafting, using branched polyethyleneimine (b-PEI) as a bridging agent. The surface morphologies and chemical structures of PBO fibers were characterized for confirming the formation of covalent bond between GO and PBO fibers. The surface roughness ( Ra ) and wettability of the obtained fibers, denoted as PBO@PDA-PEI-GO, were obviously increased in comparison with those of untreated one. The reinforcement offered a 68.8% enhancement in the interfacial shear strength (IFSS) without degrading the base fiber. The PDA layer on the PBO fiber surface led to improved UV resistance. The hydrothermal aging resistance of PBO/epoxy composite was also greatly improved. This biomimic surface modification approach is facile to prepare, highly efficient to enhance interface, adaptable to all high-performance fibers, and meaningful in multifunctional applications.